Decision Support System to Determine the Best Employees at Yogi Banyumas Repair Shop using Topsis Method - Banu Dwi Putranto; Ari Waluyo; Abdul Azis; Ranggi Praharaningtyas Aji; Riska Praise (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2022)
The assessment system to determine the best employees at the Yogi shop has not been systemized. It is still limited to the regular assessment assessing the best employees to get an annual bonus based on the owner and manager's assessment, so it seems less accurate and less targeted towards employees who will be given annual bonuses. This study aims to build a decision support system to determine the best employees using the TOPSIS method to make it easier for owners and managers to determine the best employees. The data processing method in this study is the TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) method. The criteria used in this research are attendance, work attitude, responsibility, discipline, cooperation and creativity. From the results of the tests, it concluded that the blackbox testing process was successful. The results of this study are a decision support system to determine the best employees at the Yogi Banyumas store.